The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s11270-010-0615-6
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchin Embryotoxicity Test for Environmental Contaminants—Potential Role of the MRP Proteins

Abstract: The main goals of this study were (1) to standardize a simple and reliable embryotoxicity test for environmental contaminants and (2) to evaluate the presence and possible protective role of the multidrug resistance-associated (MRP) protein-mediated multixenobiotic defense in two Mediterranean sea urchin species, Paracentrotus lividus and Arbacia lixula. Toxic end-point used was the success of the first cell division in sea urchin embryos. Embryotoxicities of three environmentally relevant contaminants: mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…This was suggested by the fact that inhibitors of MDR transporters sensitize embryos to environmental toxicants (Bosnjak et al, ) as well as chemotherapy drugs such as vinblastine (Hamdoun et al, ; De Souza et al, ; Anselmo et al, ) and etoposide (Epel et al, ). Pollutants such as mercuric chloride (Bosnjak et al, ) and antifouling agents (Bosnjak et al, ; Xu et al, ) were also shown to be substrates of MDR transporters. In addition to protecting embryos from chemical insults, transporters protect against ultraviolet radiation, albeit the mechanism remains unknown (Leite et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was suggested by the fact that inhibitors of MDR transporters sensitize embryos to environmental toxicants (Bosnjak et al, ) as well as chemotherapy drugs such as vinblastine (Hamdoun et al, ; De Souza et al, ; Anselmo et al, ) and etoposide (Epel et al, ). Pollutants such as mercuric chloride (Bosnjak et al, ) and antifouling agents (Bosnjak et al, ; Xu et al, ) were also shown to be substrates of MDR transporters. In addition to protecting embryos from chemical insults, transporters protect against ultraviolet radiation, albeit the mechanism remains unknown (Leite et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been described that NOM has the potential to modify the MXR activity in freshwater amphipods Eulimnogammarus cyaneus and Eulimnogammarus verrucosus being dissolved humic substances a potential responsible for this inhibition (Steinberg et al 2006;Timofeyev et al 2007). Interestingly, specific inhibition of MRP protein caused a significant increase in toxic potency of polluted seawater samples in embryos of sea urchin (Bošnjak et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we decided to use the purple sea urchin Paracentrotus lividus (Lamarck, 1816) since it is widely used as a model species in many ecotoxicological studies, being considered a good bioindicator of environmental change (Bellas 2008;Bonaventura et al 2011;Bošnjak et al 2011;Dinnel et al 1988;Kobayashi and Okamura 2004;Matranga et al 2000;Morale et al 1998;Pinsino et al 2010;Sconzo et al 1995;Zito et al 2005). Furthermore, the species has a key role in shaping benthic marine communities in the Mediterranean Sea and Atlantic Ocean (Guidetti et al 2003;Guidetti 2004;Sala and Zabala 1996), where it also represents an important commercial resource (Bertocci et al 2014).…”
Section: Introductionmentioning
confidence: 99%